Strategic and Tactical Tasks Development of the Arctic Zone of the Russian Federation - M. M. Kucheryavy (Управленческое консультирование, 2019)
The article analyzes the geopolitical and military-strategic importance of the Arctic. External and internal threats to the development of this region are ascertained. The author notes the competencies of St. Petersburg in solving strategic management tasks during the socioeconomic development of the Arctic. The course of work on the substantiation of the external borders of the continental shelf of the Russian Federation in the Arctic Ocean is considered. The competencies that St. Petersburg has in developing the Arctic are substantiated.